Review of Government Policies on Special Needs Education in Uganda - Otyola, Wandera Roberts; Siraji, Kamulegeya; Laaki , Samson; Shafik, Muguda; Nkurikimana, Gerald; Yoweri, Rwakasole; Ampairwe, Rose; Mukisa, Jonathan8 (American Journal of Education and Practice, 2023)
Purpose: The purpose was to review the government policies on special needs education in Uganda. It was carried out using a qualitative Document analysis method to collect data on inclusive education in Uganda. The study was guided by six objectives: to review policies on inclusivity, teacher education and disability, to review policies on teacher education and special needs education, to identify conventions, laws and policies that promote inclusive education in Uganda, to review policies on teacher capacity to handle inclusive education and career related policy issues, to identify the gaps in the policies, to identify the challenges of inclusive education in general. Findings: Summarized findings from the analysis and interviews highlight the promotion of inclusivity, teacher education, and disability awareness in Uganda's policies. The inclusion of disabled children has been a key focus, as emphasized by the United Nations' Convention on the Rights of Persons with Disabilities, calling for an end to segregation in educational settings. However, challenges persist in achieving equitable access to quality education for all learners, including millions of children out of school, disparities in access and learning outcomes, and gender inequalities. Students with disabilities face obstacles to quality education in both developed and developing countries. Implications to Theory, Practice and Policy: The report stresses the importance of addressing these challenges to ensure the effective implementation of inclusive education in Uganda. The report also recommends the amendment of the archaic laws or policies such as the UNEB Act, 1983, NCDC Act.